PENGARUH LIVE STREAMER DAN PROMO TANGGAL KEMBAR TERHADAP IMPULSIVE BUYING (STUDI KASUS PENGGUNA E- COMMERCE SHOPEE DI KOTA MATARAM) - NILA RAHAYU; DEWI RAKHMAWATI; I GUSTI AGUNG ARISTA (GANEC SWARA, 2024)
One of the biggest developments in the business sector over the past few decades is the rise of e-commerce. With the help of Shopee Live, vendors can host live streaming events and market their goods directly to customers. Broadcasters, sometimes known as streamers, organize live shopping events to highlight items and encourage customers to complete the transaction process. Shopee often holds promotions on twin dates with various attractive incentives that encourage customers to make impulse purchases. The purpose of this study is to examine the effect of twin date promotions and steamer on the impulse buying habits of Shopee customers in Mataram city. One hundred respondents who met the criteria were included in the research sample, which was selected through a purposive sampling approach. The research findings show that live steamer has no effect on impulsive buying on Shopee users in Mataram City while twin date promos have a significant effect on impulsive buying on Shopee users in Mataram City